Companion Animals Welfare in Non-Epidemic Emergencies: The Case of Central Italy, Post-Earthquake 2016/2017 - Villa, P. Dalla (Journal of applied animal ethics research, 2019)
Among the several factors affecting animal welfare, non-epidemic emergencies are very stressful events. In the aftermath of earthquakes or during flooding, snowstorms and wildfires, companion animals are subject to injuries and deep stress, abandonment or loss resulting in the overcrowding of animal shelters, or in emergent free-roaming populations representing a potential public health threat to the affected communities. The loss of animals often also results in significant psychological trauma for their guardians. For these reasons in all phases of calamities, the care of companion animals becomes essential. This paper describes the activities that were carried out for the veterinary care of dogs and cats affected by the earthquakes that occurred in central Italy from August 2016 to January 2017. These disasters provided an opportunity to test an integrated emergency management system in which several actors participated to aid, assist and accommodate the companion animals, whether owned or strays, affected by the catastrophic events.